Toxicity assessment of total petroleum hydrocarbons in aquatic environments using the bioluminescent bacterium Aliivibrio fischeri - Marzieh Mirjani; Mohsen Soleimani; Vahid Salari (Ecotoxicology and Environmental Safety, 2021)
Toxicity monitoring of environmental pollutants especially petroleum hydrocarbons as priority pollutants is an important environmental issue. This study addresses a rapid, sensitive and cost effective method for the detection of total petroleum hydrocarbons (TPHs) using Aliivibrio fischeri bioluminescence inhibition bioassay. At the first step, the optimum conditions including time, pH and temperature for growth of A. fischeri were determined. Then, two methods were used to evaluate the toxicity of petroleum compounds. In the first method, short-term (15 min) and long-term (16 h) toxicity assays were performed. In the second method luminescence kinetics of A. fischeri was investigated during 24 h. The results demonstrated the most appropriate time for the bacterial growth occurred 16 h after inoculation and optimum temperature and pH were found 25 °C and 7, respectively. Short-term and long-term toxicity did not indicate any toxicity for various concentrations of TPHs (30, 50, 110, 160, 220 mg/L). Considering the luminescence kinetics of A. fischeri the long-term assay was introduced as 6 h. The half maximal effective concentration (EC50) was achieved 1.77 mg/L of TPHs. It is concluded that the luminescence kinetics of A. fischeri can be a valuable approach for assessing toxicity of TPHs in aquatic environments.